Application of leaf multispectral analyzer in comparison to hyperspectral device to assess the diversity of spectral reflectance indices in wheat genotypes - Filacek Andrej; Zivcak Marek; Barboricova Maria; Kovar Marek; Halabuk Andrej; Gerhatova Katarina; Yang Xinghong; Hauptvogel Pavol; Brestic Marian (Open Life Sciences)
Multispectral devices have a huge potential to be utilized in biological, ecological, and agricultural studies, providing valuable information on plant structure and chemical composition. The aim of the study was to assess the reliability and sensitivity of the affordable leaf spectrometer PolyPen (PP) in comparison with the highly sensitive analytical device FieldSpec-4. Measurements at the leaf level were realized on a collection of 24 diverse field-grown wheat (Triticum sp. L.) genotypes in several growth phases during the regular growing season, focusing on whole spectral curves and a set of 41 spectral reflectance indices. As expected, the sensitive analytical device showed a higher capacity to capture genotypic variability and the ability to distinguish seasonal changes compared to a low-cost multispectral device. Nevertheless, the analysis of the data provided by low-cost sensors provided a group of parameters with good sensitivity, including reasonable correlations between the records of the two devices (r > 0.80). Based on the large obtained datasets, we can conclude that the application of a low-cost PP leaf spectrometer in plant and crop studies can be efficient, but the selection of parameters is crucial. Thus, the present study provides valuable information for users of affordable leaf spectrometers in fundamental and applied plant science.